2020
DOI: 10.1155/2020/5381012
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Single and Multiple Thyroid Nodules and Its Association with Metabolic Diseases in Chinese: A Cross-Sectional Study

Abstract: Purpose. The present study aims to investigate the prevalence of single and multiple thyroid nodules and its association with metabolic diseases in subjects who participated in the heath examination in China. Methods. This is a cross-sectional study. The participants who attend the physical examination at the Health Management Center of Southwest Hospital, Army Military Medical University, between January 2014 and December 2018, were included. Thyroid nodules were diagnosed by thyroid ultrasound. Multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
5
14
3
1
Order By: Relevance
“…The results of this study show that gender is a non-significant risk factor for thyroid lesions, and its prevalence in women is higher than that in men, which is consistent with the previous reports [19,23]. But other studies [15][16][17] show that gender is an independent risk factor for occurrence of thyroid lesions. The high incidence of thyroid lesions in women is associated with increased demand for thyroid hormones during pregnancy, breastfeeding, and menstruating; estrogen can also affect the development of thyroid nodules [27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study show that gender is a non-significant risk factor for thyroid lesions, and its prevalence in women is higher than that in men, which is consistent with the previous reports [19,23]. But other studies [15][16][17] show that gender is an independent risk factor for occurrence of thyroid lesions. The high incidence of thyroid lesions in women is associated with increased demand for thyroid hormones during pregnancy, breastfeeding, and menstruating; estrogen can also affect the development of thyroid nodules [27].…”
Section: Discussionsupporting
confidence: 91%
“…It is also consistent with the findings of Dauksiene et al [24], who studied the factors associated with thyroid nodules in Lithuanian subjects and noted that thyroid nodules represent 31.2%. Other countries have nearly similar prevalence of thyroid nodules (China 32.4% and Korea 34.2%) [15,16]. The patterns of cystic thyroid lesions observed in this study were not comparable with other available literature; cystic thyroid lesion was observed in 6.8% of our participants.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Moreover, it is partly in line with that in Korea (13.4%) [ 20 ] and Brazil (17.0%) [ 21 ]. Many epidemiological studies [ 22 24 ] have presented that the prevalence of thyroid nodules increases with age. The mechanism may be that the thyroid will undergo degenerative changes with age, resulting in development of nodules [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…2The structure of intrahepatic duct is not clearly displayed. 3The fareld echo of liver is gradually attenuated [17].…”
Section: Diagnosis Of Nafldmentioning
confidence: 99%